2018
DOI: 10.18485/aeletters.2018.3.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Application of Renewable Energy Sources in Terms of Economic, Environmental and Social Sustainability

Abstract: Abstract:We are witnesses of everyday changes, which can bring the world into the question of survival. On the other hand, the progress and the speed of changes are the keys of success. What is important is that we have to change the human being's life, due to the concept of the sustainable development, which includes three dimensions: ecology, economy and social aspect. This paper gives the analysis of using the renewable energy, through the production of the electricity, including the sustainable development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Consumer activities in a winery or wine club [48] are crucial for developing and strengthening loyalty to certain brands. Wine tourists plan their visits based on certain information (size of winery, length of stay in the wine region), including various motivating factors [46,[49][50][51][52][53][54]. Educating visitors and other potential consumers is important in building brand loyalty and improving the winery's business performance [55,56].…”
Section: Business Performance Of the Winerymentioning
confidence: 99%
“…Consumer activities in a winery or wine club [48] are crucial for developing and strengthening loyalty to certain brands. Wine tourists plan their visits based on certain information (size of winery, length of stay in the wine region), including various motivating factors [46,[49][50][51][52][53][54]. Educating visitors and other potential consumers is important in building brand loyalty and improving the winery's business performance [55,56].…”
Section: Business Performance Of the Winerymentioning
confidence: 99%
“…A study by the National Renewable Energy Laboratory found that the sun's energy falls on the world in one hour more than the entire planet consumes each year. There are various uses for solar energy these days, such as heating residences and businesses and heating water and powering electrical gadgets [21].…”
Section: Solar Energymentioning
confidence: 99%
“…Globally, everyone must adhere to the ideology of sustainable development to meet the needs of the present without jeopardising the ability of future generations to meet their own. Determining how to use, conserve, and sustainably restore resources is also a part of sustainable development, as is realising that our choices today will majorly impact future generations [21].…”
Section: Application Of Renewable Energy Sources (Res)mentioning
confidence: 99%
“…The last century was predominantly marked by the use of fossil fuels in energy production [19], but the beginning of the twenty-first century saw enormous efforts made in order to mitigate the effects of global warming caused by CO 2 emissions in the atmosphere [20]. Those were the exact endeavors in which sustainable development was grounded, a development that implies keeping a balance between the use, saving, and renewal of all resources [21], and not their uncontrolled expenditure to the detriment of future generations [22].…”
Section: The Justification For the Utilization Of Agricultural Biomasmentioning
confidence: 99%